PENATALAKSANAAN HOLISTIK KRISIS HIPERTENSI PADA PASIEN GERIATRI DENGAN SIKAP NEGATIF TERHADAP KEPATUHAN PENGOBATAN, SELF-MONITORING DAN MODIFIKASI GAYA HIDUP MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS GEDONG AIR - Cassa Victoria Regia Divandra; dr. Diana Mayasari, M.K.K (Medula, 2023)
Hypertensive crisis is a condition where systolic blood pressure is 180 mmHg and/or diastolic is 120 mmHg. Hypertension rarely causes symptoms, so it can cause other morbidities that are often not recognized. The prevalence of hypertension in Indonesia based on Riskesdas 2018 increased by 34.1% compared to 2013 which was 25.8%. Applying the principle of a family doctor approach in detecting internal and external risk factors and solving EBM (Evidence Based Medicine) based problems. This study is a Case Report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. Mrs. M, 63 years old, has a chief complaint of throbbing headache since 2 days ago. Headaches are felt to be throbbing and occur throughout the day. The patient has a history of hypertension which has been diagnosed since 2017 but does not take the medicine regularly. Furthermore, interventions were carried out using poster media and daily checklists regarding symptoms, causes, risk factors, ways of controlling, complications, low-fat diet and limiting salt consumption and physical activity for people with hypertension. Management with a family medicine approach is needed for patients with Hypertensive Crisis to identify problems in various aspecs in order to support the success of therapy and improve the patient's quality of life.